Poverty Alleviation Policy in West Java Province - Siti Anah Kunyati; Didiet Widiowati (Asian Social Work Journal, 2018)
Poverty and social welfare issues show an increase over time, both in the number, and the quality. On the other hand, the policy responses to social welfare issues from various parties are not sufficient to tackle those problems. This study aims to describe poverty and policy of West Java Provincial Government in poverty alleviation. The research is expected to contribute to the improvement of policy in poverty alleviation and affect the condition of West Java society to be more prosperous. The research design is Qualitative Descriptive. The informants are several Civil State Apparatuses who are capable to represent Regional Work Unit/ Organization at the provincial level. Data Collecting Techniques consist of interviews, focus group discussions, and documentation studies. Data Validation is done using triangulation between data sources and techniques. The results showed that West Java's economy grew on average above 5%, while the average poverty reduction rate was only 0.46% per year. These conditions have an impact on the increased number of people who are below the poverty threshold and also affect the index of depth and severity of poverty. The situation is similar for other social welfare issues, such as socio-economic vulnerable groups, homeless, beggars, and scavengers, neglected elderly, and children who need social protection. To overcome those problems, several policies have been prepared. The obstacle is, social welfare planning and policy are often only viewed as a complement to development planning and policy framework when they should be considered as an integrative, priority and substantive element that must be implemented. Various regulations and policies on poverty alleviation and other social welfare issues are still limited. Regulation at the central level is sufficient, but local governments have not been fully able to describe and operationalize it with various rules, either at the level of Regional Regulation, Governor Regulation, Mayor Regulation, or Regent Regulation. Legislation regulation and poverty alleviation are government’s (central and local) full responsibility, so coordination and a common commitment are needed to address poverty and increase equity. West Java Provincial Policy needs to prioritize efforts to increase funding through funding synergies with central and district / city governments in order to finance more comprehensive and broader poverty reduction programs.